2009
DOI: 10.1371/journal.pone.0008277
|View full text |Cite
|
Sign up to set email alerts
|

Chaperonin Contributes to Cold Hardiness of the Onion Maggot Delia antiqua through Repression of Depolymerization of Actin at Low Temperatures

Abstract: Winter-diapause and cold-acclimated non-diapause pupae of the onion maggot, Delia antiqua (Diptera: Anthomyiidae), show strong cold hardiness. To obtain insights into the mechanisms involved in the enhancement of cold hardiness, we investigated the expression patterns of genes encoding subunits of chaperonin (CCT) and the morphology of actin, a substrate of CCT, at low temperatures. Quantitative real-time PCR analyses showed the mRNA levels of CCT subunits in pupal tissues to be highly correlated with the cold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…For example, cold shock can cause actin disassembly and recent studies have shown a critical role for a chaperone called CCT (chaperonin containing t-complex polypeptide-1) in stabilizing actin in vivo at low temperatures in D. antiqua. 76 Nonhardy pupae showed cold-induced depolymerization of actin but cold-hardy pupae did not and this correlated with the coordinated upregulation of all CCT subunits in cold-hardy pupae. Finally, proteins in freeze-tolerant species could also be susceptible to freeze denaturation.…”
mentioning
confidence: 93%
“…For example, cold shock can cause actin disassembly and recent studies have shown a critical role for a chaperone called CCT (chaperonin containing t-complex polypeptide-1) in stabilizing actin in vivo at low temperatures in D. antiqua. 76 Nonhardy pupae showed cold-induced depolymerization of actin but cold-hardy pupae did not and this correlated with the coordinated upregulation of all CCT subunits in cold-hardy pupae. Finally, proteins in freeze-tolerant species could also be susceptible to freeze denaturation.…”
mentioning
confidence: 93%
“…It has been reported that in non-hardy pupae of D. antiqua, cold-induced depolymerization of actin occurred while cold-hardy pupae did not, and the latter was closely related to enhanced transcript level of complex CCT in the cold-hardy larvae, demonstrating CCT could stabilize actin at low temperature (Kayukawa and Ishikawa 2009). It was also reported that plant CCTα from the mangrove tree Bruguiera sexangula showed a vital character related to salt-and osmotic-stress tolerance (Yamada et al 2002).…”
Section: Discussionmentioning
confidence: 95%
“…Meanwhile, it has been demonstrated that if the actin depolymerization was inhibited by the chemical reagent Latrunculin B, the subsequent cold hardiness of pupae of D. antiqua was compromised (Kayukawa and Ishikawa 2009). Both actin and tubulin are believed to engender depolymerization at low temperature when cytoskeleton is subjected to crumbling, which is a significant element for the occurrence of cold injuries (Upadhya and Strasberg 1999;Kayukawa et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Another chaperone, tailless complex polypeptide 1 (TCP-1) is related to Hsp60 and participates in folding a wide range of proteins, particularly those associated with the cytoskeleton (e.g. actin, tubulin) (Kayukawa et al, 2005;Kayukawa and Ishikawa, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Burton et al, 1988;Colinet et al, 2010;Stetina et al, 2015;Tungjitwitayakul et al, 2015). Recently, however, various authors have begun to show that chaperones contribute to the natural winter diapause and/or cold hardiness of insects (Sonoda et al, 2006;Kayukawa et al, 2005;Chen et al, 2006;Kayukawa and Ishikawa, 2009;Rinehart et al, 2006Rinehart et al, , 2007Yu et al, 2016); for review also see Storey and Storey (2011) and King and MacRae (2015). Indeed, work by our group has shown that larvae of the freeze tolerant goldenrod gall fly, Eurosta solidaginis, that are often found in the same fields (or even on the same plants) as E. scudderiana, up-regulate HSPs both during the winter season when larvae are in diapause and in response to laboratory cold-acclimation (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%